usun nawiasy i zredukuj wyrazy podobne
1.(a+2)(a+4)
2.(x+5)(x-3)
3.(x-6)(x+7)
4.(2x-6)(x-8)
5.(3x-2)(x+2)
6.(5x+2)(3x-2)
7.(-2x+1)(2x+1)
8.(-3x+2)(-x+2)
9.(7x-4)(-x+2)
10.(3x-2)(4x-3)
11.(-3x+2)(x+5)
12.(7y+5y)(2x+1)
13.(3x-y)(4x+y)
14.(x+2)(-x+3)
15.(x-4)9-x+5)
16(-x-4)(-x+4)


Odpowiedź :

1.(a+2)(a+4) = a² + 4a + 2a + 8 = a² + 6a + 8
2.(x+5)(x-3) = x² - 3x + 5x - 15 = x² + 2x - 15
3.(x-6)(x+7) = x² + 7x - 6x - 42 = x² + x - 42
4.(2x-6)(x-8) = 2x² - 16x - 6x + 48 = 2x² - 22 + 48
5.(3x-2)(x+2) = 3x² + 6x - 2x - 4 = 3x² + 4x - 4
6.(5x+2)(3x-2) = 15x² - 10x + 6x - 4 = 15x² - 4x - 4
7.(-2x+1)(2x+1) = -4x² - 2x + 2x +1 = -4x² + 1
8.(-3x+2)(-x+2) = 3x² - 6x - 2x + 4 = 3x² - 8x +4
9.(7x-4)(-x+2) = -7x² + 14x + 4x - 8 = -7x² + 18x - 8
10.(3x-2)(4x-3) = 12x² - 9x - 8x + 6 = 12x² - 17x + 6
11.(-3x+2)(x+5) = -3x² - 15x + 2x + 10 = -3x² - 13x + 10
12.(7y+5y)(2x+1) = 14xy + 7y + 10xy + 5y = 24xy + 12y
13.(3x-y)(4x+y) = 12x² + 3xy - 4xy - y² = 12x² - y² - xy
14.(x+2)(-x+3) = -x² + 3x - 2x + 6 = -x² +x + 6
15.(x-4)(9-x+5) = 9x - x² + 5x -36 + 4x - 20 = 18x - x² - 56
16(-x-4)(-x+4) = x² - 4x + 4x - 16 = x² - 16
1.(a+2)(a+4)=a²+4a+2a+8=a²+6a+8
2.(x+5)(x-3)=x²-3x+5x-15=x²+2x-15
3.(x-6)(x+7)=x²+7x-6x-42=x²+x-42
4.(2x-6)(x-8)=2x²-16x-6x+48=2x²-22x+48
5.(3x-2)(x+2)=3x²+6x-2x-4=3x²+4x-2x
6.(5x+2)(3x-2)=15x²-10x+6x-4=15x²-4x-4
7.(-2x+1)(2x+1)=-4x²-2x+2x+1=-4x²+1
8.(-3x+2)(-x+2)=3x²-6x-2x+4=3x²-8x+4
9.(7x-4)(-x+2)=-7x²+14x+4x-8=-7x²+18x-8
10.(3x-2)(4x-3)=12x²-9x-8x+6=12x²-17x+6
11.(-3x+2)(x+5)=-3x²-15x+2x+10=-3x²-13x+10
12.(7y+5y)(2x+1)=12y(2x+1)=24xy+12y
13.(3x-y)(4x+y)=12xy+3xy-4xy-y²=11xy-y²
14.(x+2)(-x+3)=-x²+3x-2x+6=x²+x+6
15.(x-4)9-x+5)[czy przed dziewiątką ma być nawias? - zrąbią jakby był]=9x-x²+5x-36+4x-20=-x²+18x-56
16(-x-4)(-x+4)=x²-16